Avulsion and replantation of permanent incisive:13 years of control - Gonçalves, Gláucia Beatriz [UNESP]; Tomazoli, Aline Thomazelli Peres; Iwaki, Lilian Vessoni; Endo, Marcos Sérgio; Pavan, Nair Narumi Orita (Dental Press International, 2019)
Introduction: The maintenance of a traumatized tooth in the oral cavity depends on a correct emergency treatment, as well as a long and adequate period of clinical-imaging follow-up. Objective: To report a clinical case of avulsion and replantation of tooth 11, in an 11-year-old child, who has been in the oral cavity for 13 years. Methods: tooth replantation 45 minutes after avulsion, endodontic treatment with 10 monthly exchanges of intracanal calcium hydroxide medication, followed by root canal filling using lateral condensation technique. Clinical and radiographic follow-up.Results: after 13 years of clinical and imaging control, tooth 11 presents aesthetically satisfactory function. Conclusion:The upper right central incisor, avulsed, replanted and ankylosed presented an evolutionary condition of root resorption by substitution, but inactive until the last follow-up. After endodontic treatment and clinical and imaging follow-up, the tooth remained in the oral cavity in function, without symptomatology and aesthetically pleasing after 13 years ofreplantation
Keywords: Endodontics; Tooth Avulsion; Tooth Replantation